Electrode, lithium ion secondary battery, and method for manufacturing electrode

By optimizing the ratio of conductive additive to binder in a specific region of the electrode using glow discharge spectroscopy and controlled drying conditions, the electrode and battery achieve enhanced rate characteristics for high-speed charging and discharging.

JP7618467B2Active Publication Date: 2025-01-21TDK CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021036529
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-08
Publication Date
2025-01-21
Estimated Expiration
2041-03-08

AI Technical Summary

Technical Problem

The drying conditions of the coating film in lithium ion secondary battery electrodes affect the rate characteristics, which are not clearly defined, leading to insufficient performance in high-speed charging and discharging, and the manufacturing conditions for achieving excellent rate characteristics are not established.

Method used

The electrode design includes a specific ratio of conductive additive to binder in a defined region of the active material layer, determined through glow discharge spectroscopy, with conditions optimized for drying to enhance lithium ion and electron conductivity.

Benefits of technology

The optimized electrode design results in lithium ion secondary batteries with improved rate characteristics, ensuring high electron and lithium ion conductivity, enhancing the battery's performance in rapid discharge applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007618467000002
    Figure 0007618467000002
  • Figure 0007618467000003
    Figure 0007618467000003
  • Figure 0007618467000001
    Figure 0007618467000001
Patent Text Reader

Abstract

To provide an electrode with an excellent rate characteristic, a lithium ion secondary battery, and a manufacturing method of the electrode.SOLUTION: An electrode 20 comprises: a collector 22; and an active material layer 24 contacted to at least one surface of the collector 22. The active material layer 24 contains: an active material; a conductive auxiliary; and a binder. In a first region A1 within 16.7% of a total thickness of the active material layer 24 from a front surface of the collector 22 side of the active material layer 24 to a thickness direction, a first ratio obtained by dividing a presence ratio of the conductive auxiliary calculated by performing a glow discharge spectral analysis to the active material layer 24 into the presence ratio of the binder is 94% or larger of an overall average.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrode, a lithium ion secondary battery, and a method for manufacturing the electrode. [Background technology]

[0002] Lithium ion secondary batteries are also widely used as power sources for mobile devices such as mobile phones and notebook computers, as well as hybrid cars.

[0003] An electrode for a lithium ion secondary battery is produced by drying a coating film applied onto a current collector, as described in, for example, Patent Document 1. In order to improve production efficiency, attempts have been made to speed up the drying process. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2019-169286 A Summary of the Invention [Problem to be solved by the invention]

[0005] The drying conditions of the coating film affect the performance of the electrode. One of the performances is the rate characteristic. The rate characteristic is the charge / discharge characteristic when charging / discharging at a high rate. However, it is not clear what conditions the coating film after drying must satisfy in order to have good rate characteristics. Therefore, it has not been possible to obtain electrodes with excellent rate characteristics. It has also not been possible to determine the manufacturing conditions for electrodes with excellent rate characteristics.

[0006] The present disclosure has been made in consideration of the above problems, and has an object to provide an electrode, a lithium ion secondary battery, and a method for manufacturing the electrode, which are excellent in rate characteristics. [Means for solving the problem]

[0007] The present inventors have found parameters that affect rate characteristics, and have discovered that by designing these parameters, it is possible to obtain an electrode and a lithium ion secondary battery that are excellent in rate characteristics. That is, in order to solve the above problems, the following means are provided.

[0008] (1) An electrode according to a first aspect comprises a current collector and an active material layer in contact with at least one side of the current collector, the active material layer including an active material, a conductive additive, and a binder, and in a first region of the active material layer extending from a surface of the current collector in a thickness direction within 16.7% of a total thickness of the active material layer, a first ratio obtained by dividing the abundance ratio of the conductive additive by the abundance ratio of the binder, which is determined by performing glow discharge spectroscopy on the active material layer, is 94% or more of an overall average.

[0009] (2) In the electrode according to the above aspect, the first ratio in the first region may be 130% or less of the overall average.

[0010] (3) In the electrode according to the above aspect, the difference between the first ratio in the first region and the first ratio in a region within 16.7% of the total thickness of the active material layer in a thickness direction from a surface of the active material layer opposite the current collector may be 25% or less.

[0011] (4) In the electrode according to the above aspect, the element ratio of carbon to fluorine in the binder may be 0.5 or more and 2.1 or less.

[0012] (5) A lithium ion secondary battery according to a second aspect includes the electrode according to the above aspect.

[0013] (6) A manufacturing method of a lithium ion secondary battery according to a third aspect includes a conditioning step and an actual drying step, the conditioning step including a first step of drying a coating film containing an active material, a conductive assistant, and a binder applied onto a current collector under a plurality of conditions in which at least one of a conveying speed, a drying temperature, and a drying time is changed, and a second step of analyzing each of the active material layers obtained by drying the coating film in the first step, and determining a first condition under which a first ratio, obtained by dividing the abundance ratio of the conductive assistant by the abundance ratio of the binder obtained by performing a glow discharge spectroscopy analysis on the active material layer in a first region within 16.7% of a total thickness of the active material layer in a thickness direction from a surface of the current collector, is 94% or more of an overall average, and the actual drying step is performed under the first condition. Effect of the Invention

[0014] The electrode and the lithium ion secondary battery according to the above aspect have excellent rate characteristics. Furthermore, the electrode manufacturing method according to the above aspect can produce an electrode with excellent rate characteristics. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 is a schematic diagram of a lithium ion secondary battery according to a first embodiment. [Diagram 2] FIG. 2 is a cross-sectional view of a positive electrode according to the first embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, the embodiments will be described in detail with reference to the drawings as appropriate. The drawings used in the following description may show characteristic parts in an enlarged scale for the sake of convenience in order to make the characteristics easier to understand, and the dimensional ratios of each component may differ from the actual ones. The materials, dimensions, etc. exemplified in the following description are merely examples, and the present invention is not limited thereto, and may be appropriately modified and implemented within the scope of the present invention.

[0017] "Lithium-ion secondary battery" Fig. 1 is a schematic diagram of a lithium ion secondary battery according to a first embodiment. The lithium ion secondary battery 100 shown in Fig. 1 includes a power generating element 40, an exterior body 50, and a non-aqueous electrolyte (not shown). The exterior body 50 covers the periphery of the power generating element 40. The power generating element 40 is connected to the outside via a pair of connected terminals 60, 62. The non-aqueous electrolyte is contained within the exterior body 50.

[0018] (Power generation element) The power generating element 40 includes a positive electrode 20, a negative electrode 30, and a separator 10.

[0019] <Positive electrode> The positive electrode 20 includes, for example, a positive electrode current collector 22 and a positive electrode active material layer 24. The positive electrode active material layer 24 is in contact with at least one surface of the positive electrode current collector 22.

[0020] [Positive electrode current collector] The positive electrode current collector 22 is, for example, a conductive plate material. The positive electrode current collector 22 is, for example, a thin metal plate made of aluminum, copper, nickel, titanium, stainless steel, etc. The average thickness of the positive electrode current collector 22 is, for example, 10 μm or more and 30 μm or less.

[0021] [Cathode active material layer] The positive electrode active material layer 24 includes, for example, a positive electrode active material, a conductive assistant, and a binder.

[0022] The positive electrode active material can be an electrode active material that can reversibly absorb and release lithium ions, remove and insert (intercalate) lithium ions, or dope and dedope lithium ions with counter anions.

[0023] The positive electrode active material is, for example, a composite metal oxide. The composite metal oxide is, for example, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2), lithium manganese spinel (LiMn2O4), and a lithium manganese oxide represented by the general formula: LiNi x Co y Mn z M aA compound of O2 (where x + y + z + a = 1, 0 ≦ x < 1, 0 ≦ y < 1, 0 ≦ z < 1, 0 ≦ a < 1 in the general formula, and M is one or more elements selected from Al, Mg, Nb, Ti, Cu, Zn, Cr), a lithium vanadium compound (LiV2O5), olivine-type LiMPO4 (where M represents one or more elements selected from Co, Ni, Mn, Fe, Mg, Nb, Ti, Al, Zr or VO), lithium titanate (Li4Ti5O 12 ), LiNi x Co y Al z O2 (0.9 < x + y + z < 1.1). The positive electrode active material may be an organic substance. For example, the positive electrode active material may be polyacetylene, polyaniline, polypyrrole, polythiophene, or polyacene.

[0024] The conductive assistant enhances the electron conductivity between the active materials. The conductive assistant is, for example, carbon powder such as carbon black and ketjen black, carbon nanotubes, carbon materials, metal fine powders such as copper, nickel, stainless steel, and iron, a mixture of a carbon material and a metal fine powder, or a conductive oxide such as ITO. Carbon materials such as carbon black and ketjen black are preferred as the conductive assistant.

[0025] The binder binds the active materials together. Known binders can be used. For example, the binder is a fluororesin. The fluororesin is, for example, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), tetrafluoroethylene - hexafluoropropylene copolymer (FEP), tetrafluoroethylene - perfluoroalkyl vinyl ether copolymer (PFA), ethylene - tetrafluoroethylene copolymer (ETFE), polychlorotrifluoroethylene (PCTFE), ethylene - chlorotrifluoroethylene copolymer (ECTFE), polyvinyl fluoride (PVF), etc.

[0026] In addition to the above, the binder may be, for example, vinylidene fluoride-based fluororubber such as vinylidene fluoride-hexafluoropropylene-based fluororubber (VDF-HFP-based fluororubber), vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene-based fluororubber (VDF-HFP-TFE-based fluororubber), vinylidene fluoride-pentafluoropropylene-based fluororubber (VDF-PFP-based fluororubber), vinylidene fluoride-pentafluoropropylene-tetrafluoroethylene-based fluororubber (VDF-PFP-TFE-based fluororubber), vinylidene fluoride-perfluoromethylvinylether-tetrafluoroethylene-based fluororubber (VDF-PFMVE-TFE-based fluororubber), or vinylidene fluoride-chlorotrifluoroethylene-based fluororubber (VDF-CTFE-based fluororubber). The binder may be, for example, cellulose, styrene-butadiene rubber, ethylene-propylene rubber, polyimide resin, polyamide-imide resin, acrylic resin, or the like.

[0027] 2 is an enlarged cross-sectional view of a characteristic portion of the positive electrode 20 according to this embodiment. The positive electrode active material layer 24 is on the positive electrode current collector 22. The positive electrode active material layer 24 can be divided into a plurality of regions in the thickness direction. The positive electrode active material layer 24 shown in FIG. 2 is divided into six regions in the thickness direction, each region being 16.7% of the total thickness. These regions are referred to as a first region A1, a second region A2, a third region A3, a fourth region A4, a fifth region A5, and a sixth region A6, in that order from the positive electrode current collector 22.

[0028] The first ratio of the first region A1 is 94% or more of the overall average. The first ratio of the first region A1 is preferably 130% or less of the overall average, and more preferably 107% or less.

[0029] The first ratio is a ratio obtained by dividing the abundance ratio of the conductive assistant by the abundance ratio of the binder in a specific region of the positive electrode active material layer 24. The first ratio is determined by using glow discharge spectroscopy. A specific method for determining the first ratio will be described.

[0030] First, glow discharge spectroscopy is performed on the positive electrode active material layer 24. Glow discharge spectroscopy is a method for measuring the element distribution in the thickness direction of a thin film by irradiating a sample surface with rare gas ions to release atoms from the sample and continuously analyzing the emission lines of the atoms.

[0031] First, fluorine element is analyzed by glow discharge spectroscopy. Fluorine element is contained only in the binder in the positive electrode active material layer 24. Therefore, the element ratio of fluorine element can be converted into the existence ratio of the binder in the positive electrode active material layer 24. Since glow discharge spectroscopy can measure the element distribution in the thickness direction as described above, the existence ratio of the binder in each of the first region A1 to the sixth region A6 can be obtained.

[0032] Next, carbon element is analyzed by glow discharge spectroscopy. Carbon element is contained in the binder and the conductive assistant in the positive electrode active material layer 24. Therefore, the abundance ratio of the conductive assistant in the positive electrode active material layer 24 cannot be directly converted from the element ratio of carbon element in the positive electrode active material layer 24. Therefore, the positive electrode active material layer 24 is subjected to a process for removing the carbon element caused by the binder from the element ratio of carbon element.

[0033] First, only the binder is formed on the underlayer. The binder is the same as the binder contained in the positive electrode active material layer 24. Glow discharge spectroscopy is performed on the binder. From the results of the glow discharge spectroscopy, the elemental ratio (C / F) of the carbon element to the fluorine element contained in the binder is obtained. The elemental ratio (C / F) is, for example, 0.5 or more and 2.1 or less.

[0034] Next, the elemental ratio of the carbon element attributable to the binder in the positive electrode active material layer 24 is calculated by multiplying the elemental ratio of the fluorine element in the positive electrode active material layer 24 obtained previously by the elemental ratio of the carbon element to the fluorine element contained in the binder (C / F). Next, the elemental ratio of the carbon element attributable to the conductive assistant is obtained by subtracting the elemental ratio of the carbon element attributable to the binder from the elemental ratio of the carbon element in the positive electrode active material layer 24. The elemental ratio of the carbon element attributable to the conductive assistant can be converted into the abundance ratio of the conductive assistant in the positive electrode active material layer 24. Since the glow discharge spectroscopy can measure the elemental distribution in the thickness direction as described above, the abundance ratio of the conductive assistant in each of the first region A1 to the sixth region A6 can be obtained.

[0035] The first ratio is then calculated by dividing the calculated proportion of the conductive additive by the proportion of the binder. The overall average of the first ratio is calculated by averaging the values ​​calculated for each region.

[0036] The first ratio of the sixth region A6 is preferably, for example, 119% or less of the overall average. The difference between the first ratio of the first region A1 and the first ratio of the sixth region A6 is preferably 25% or less.

[0037] <Negative electrode> The negative electrode 30 includes, for example, a negative electrode current collector 32 and a negative electrode active material layer 34. The negative electrode active material layer 34 is formed on at least one surface of the negative electrode current collector 32.

[0038] [Negative electrode current collector] The negative electrode current collector 32 is, for example, a conductive plate material. The negative electrode current collector 32 may be the same as the positive electrode current collector 22.

[0039] [Negative electrode active material layer] The negative electrode active material layer 34 contains a negative electrode active material and may further contain a conductive assistant, a binder, and a solid electrolyte, as necessary.

[0040] The negative electrode active material may be any compound capable of occluding and releasing ions, and known negative electrode active materials used in lithium ion secondary batteries can be used. Examples of the negative electrode active material include metallic lithium, lithium alloys, graphites (natural graphite, artificial graphite) capable of occluding and releasing ions, carbon nanotubes, carbon materials such as non-graphitizable carbon, graphitizable carbon, and low-temperature calcined carbon, metals such as aluminum, silicon, tin, and germanium that can combine with metals such as lithium, SiO x (0 < x < 2), amorphous compounds mainly composed of oxides such as tin dioxide, particles containing lithium titanate (Li4Ti5O 12 ) and the like.

[0041] The negative electrode active material layer 34 may contain silicon, tin, or germanium. Silicon, tin, or germanium may exist as a single element or as a compound. The compound is, for example, an alloy, an oxide, or the like. As an example, when the negative electrode active material is silicon, the negative electrode 30 may be called an Si negative electrode. The negative electrode active material may be, for example, a mixed system of a single substance or a compound of silicon, tin, or germanium and a carbon material. The carbon material is, for example, natural graphite. Further, the negative electrode active material may be, for example, a single substance or a compound of silicon, tin, or germanium whose surface is coated with carbon. The carbon material and the coated carbon enhance the conductivity between the negative electrode active material and the conductive assistant. When the negative electrode active material layer contains silicon, tin, or germanium, the capacity of the lithium ion secondary battery 100 increases.

[0042] The negative electrode active material layer 34 may contain lithium, for example, as described above. The lithium may be metallic lithium or a lithium alloy. The negative electrode active material layer 34 may be metallic lithium or a lithium alloy. The lithium alloy is, for example, an alloy of one or more elements selected from the group consisting of Si, Sn, C, Pt, Ir, Ni, Cu, Ti, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Sb, Pb, In, Zn, Ba, Ra, Ge, and Al, and lithium. As an example, when the negative electrode active material is metallic lithium, the negative electrode 30 may be called an Li negative electrode. The negative electrode active material layer 34 may be a sheet of lithium.

[0043] The negative electrode 30 may not have the negative electrode active material layer 34 during fabrication, and may comprise only the negative electrode current collector 32. When the lithium-ion secondary battery 100 is charged, metallic lithium is precipitated on the surface of the negative electrode current collector 32. Metallic lithium is elemental lithium from which lithium ions have been precipitated, and the metallic lithium functions as the negative electrode active material layer 34.

[0044] The conductive assistant and binder may be the same as those in the positive electrode 20. The binder in the negative electrode 30 may be, for example, cellulose, styrene-butadiene rubber, ethylene-propylene rubber, polyimide resin, polyamide-imide resin, acrylic resin, etc., in addition to those listed in the positive electrode 20. The cellulose may be, for example, carboxymethyl cellulose (CMC).

[0045] <separator> The separator 10 is sandwiched between the positive electrode 20 and the negative electrode 30. The separator 10 separates the positive electrode 20 from the negative electrode 30 and prevents a short circuit between the positive electrode 20 and the negative electrode 30. The separator 10 extends in-plane along the positive electrode 20 and the negative electrode 30. Lithium ions can pass through the separator 10.

[0046] The separator 10 has, for example, an electrically insulating porous structure. The separator 10 may be, for example, a monolayer or laminate of a film made of a polyolefin such as polyethylene or polypropylene, or a stretched film of a mixture of the above resins, or a fibrous nonwoven fabric made of at least one material selected from the group consisting of cellulose, polyester, polyacrylonitrile, polyamide, polyethylene, and polypropylene. The separator 10 may be, for example, a solid electrolyte. The solid electrolyte may be, for example, a polymer solid electrolyte, an oxide-based solid electrolyte, or a sulfide-based solid electrolyte.

[0047] (Terminal) The terminals 60 and 62 are connected to the positive electrode 20 and the negative electrode 30, respectively. The terminal 60 connected to the positive electrode 20 is a positive electrode terminal, and the terminal 62 connected to the negative electrode 30 is a negative electrode terminal. The terminals 60 and 62 are responsible for electrical connection to the outside. The terminals 60 and 62 are made of a conductive material such as aluminum, nickel, or copper. The connection method may be welding or screwing. The terminals 60 and 62 are preferably protected with insulating tape to prevent short circuits.

[0048] (Exterior body) The power generating element 40 and the non-aqueous electrolyte are sealed inside the exterior body 50. The exterior body 50 prevents the non-aqueous electrolyte from leaking to the outside and prevents moisture and the like from entering the lithium-ion secondary battery 100 from the outside.

[0049] 1, the exterior body 50 has a metal foil 52 and a resin layer 54 laminated on each side of the metal foil 52. The exterior body 50 is a metal laminate film in which the metal foil 52 is coated on both sides with a polymer film (resin layer 54).

[0050] For example, aluminum foil can be used as the metal foil 52. A polymer film such as polypropylene can be used as the resin layer 54. The materials constituting the resin layer 54 may be different between the inside and outside. For example, a polymer with a high melting point such as polyethylene terephthalate (PET) or polyamide (PA) can be used as the material for the outside, and polyethylene (PE), polypropylene (PP), etc. can be used as the material for the polymer film on the inside.

[0051] (Non-aqueous electrolyte) The non-aqueous electrolyte is sealed in the exterior body 50 and impregnates the power generating element 40. The non-aqueous electrolyte includes, for example, a non-aqueous solvent and an electrolyte. The electrolyte is dissolved in the non-aqueous solvent.

[0052] The non-aqueous solvent contains, for example, a cyclic carbonate and a chain carbonate. The cyclic carbonate solvates the electrolyte. The cyclic carbonate is, for example, ethylene carbonate, propylene carbonate, and butylene carbonate. The cyclic carbonate preferably contains at least propylene carbonate. The chain carbonate reduces the viscosity of the cyclic carbonate. The chain carbonate is, for example, diethyl carbonate, dimethyl carbonate, and ethyl methyl carbonate. The non-aqueous solvent may also contain methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, and the like.

[0053] The volume ratio of the cyclic carbonate to the chain carbonate in the non-aqueous solvent is preferably 1:9 to 1:1.

[0054] The electrolyte is, for example, a lithium salt. The electrolyte is, for example, LiPF6, LiClO4, LiBF4, LiCF3SO3, LiCF3CF2SO3, LiC(CF3SO2)3, LiN(CF3SO2)2, LiN(CF3CF2SO2)2, LiN(CF3SO2)(C4F9SO2), LiN(CF3CF2CO)2, LiBOB, etc. The lithium salt may be used alone or in combination of two or more. From the viewpoint of the degree of ionization, it is preferable that the electrolyte contains LiPF6.

[0055] "Method of manufacturing lithium-ion secondary batteries" First, the positive electrode 20 is produced. When producing the positive electrode 20, a condition determination step is first performed to define the manufacturing conditions of the positive electrode 20. The actual drying step is performed based on the conditions (first conditions) obtained in the condition determination step.

[0056] The conditioning process has two steps: Step 1 and Step 2. Step 1 is a process of drying the coating film under various conditions. Step 2 is a process of analyzing the dried coating film and extracting the appropriate conditions.

[0057] The first step is performed as follows. First, a paste-like positive electrode slurry (coating) is applied to at least one surface of the positive electrode collector 22. A commercially available positive electrode collector 22 can be used. There are no particular limitations on the application method. Examples include a slit die coating method and a doctor blade method. The positive electrode slurry is a paste made by mixing a positive electrode active material, a conductive assistant, a binder, and a solvent.

[0058] Next, the positive electrode slurry is dried to remove the solvent. The positive electrode slurry is dried, for example, by passing it through a drying furnace. Examples of drying conditions include the conveying speed of the positive electrode current collector 22 coated with the positive electrode slurry, the drying temperature, the drying time, and the gas speed relative to the positive electrode slurry. The drying temperature and the drying time each have conditions for the coating film preheating period, the coating film temperature holding period, and the coating film temperature increasing period. That is, there are parameters for the drying temperature and drying time in the coating film preheating period, the drying temperature and drying time in the coating film temperature holding period, and the drying temperature and drying time in the coating film temperature increasing period. In the first step, the coating film is dried under a plurality of conditions in which at least one of the conveying speed, the drying temperature, and the drying time is changed.

[0059] In the second step, glow discharge spectroscopy is performed on the positive electrode active material layers 24 produced under each of the multiple conditions. The glow discharge spectroscopy is performed to determine the first ratio of each positive electrode active material layer 24. Then, a condition (first condition) under which the first ratio of the first region A1 is 94% or more of the overall average is extracted.

[0060] When the temperature during the coating preheating period and the coating temperature holding period is 90°C or less, the first condition tends to be met. It is believed that a high drying temperature increases the removal rate of the solvent on the surface of the positive electrode slurry, which makes it easier for the binder to segregate on the surface of the positive electrode slurry. Segregation of the binder inhibits convection in the positive electrode slurry. Also, when the coating temperature holding period at a temperature of 90°C or less is 40 seconds or more, the first condition tends to be met. Also, when the conveying speed is 9.5 m / min or less, the first condition tends to be met.

[0061] The positive electrode 20 is produced by carrying out an actual drying step based on the results of the above-mentioned condition setting step. The actual drying step is carried out under the first condition determined in the condition setting step. The dried coating film may then be pressed to densify the positive electrode active material layer 24. For example, a roll press machine, a hydrostatic press machine, or the like may be used as the pressing means.

[0062] Next, the negative electrode 30 is prepared. The negative electrode 30 can be prepared in the same manner as the positive electrode 20. A paste-like negative electrode slurry is applied to at least one surface of the negative electrode current collector 32. The negative electrode slurry is prepared by mixing a negative electrode active material, a binder, a conductive assistant, and a solvent to form a paste. The negative electrode slurry is applied to the negative electrode current collector 32 and dried to obtain the negative electrode 30.

[0063] Next, the prepared positive electrode 20 and negative electrode 30 are laminated so that the separator 10 is located between them to prepare the power generating element 40. When the power generating element 40 is a wound body, the positive electrode 20, the negative electrode 30, and one end side of the separator 10 are wound around the axis.

[0064] Finally, the power generating element 40 is enclosed in the exterior body 50. A non-aqueous electrolyte is injected into the exterior body 50. After the injection of the non-aqueous electrolyte, the pressure is reduced, heating, etc. is performed, so that the non-aqueous electrolyte is impregnated into the power generating element 40. The exterior body 50 is sealed by applying heat, etc., to obtain the lithium ion secondary battery 100.

[0065] As shown in the examples described later, the lithium ion secondary battery according to the first embodiment has improved rate characteristics because the first ratio in the first region A1 satisfies the above-mentioned condition.

[0066] Although the reason for this is not clear, it is believed that the first region A1 is located closest to the positive electrode current collector 22 and has a large effect on the rate characteristics. The rate characteristics are the capacity retention rate when rapidly discharged, based on the 0.2C discharge capacity after 0.2C CCCV charging. The higher the rate characteristics, the more the battery can perform adequately during rapid discharge. The lithium ion conductivity and electronic conductivity in the active material layer have a large effect on the rate characteristics.

[0067] The first ratio in the first region A1 being 94% or more of the overall average means that a sufficient conductive assistant is present in the first region A1. If the amount of conductive assistant in the first region A1 is sufficient, the electronic conductivity in the positive electrode active material layer 24 can be sufficiently ensured. In addition, the conductive assistant has high liquid retention. Therefore, if the amount of conductive assistant in the first region A1 is sufficient, a sufficient electrolyte is present in the first region A1. The electrolyte is responsible for the conduction of lithium ions between the positive electrode active materials. Therefore, the lithium ion conductivity in the positive electrode active material layer 24 can also be ensured. In other words, if the first ratio in the first region A1 is 94% or more of the overall average, the lithium ion conductivity and electronic conductivity in the first region A1 become sufficiently high, and it is considered that the rate characteristics are improved.

[0068] Furthermore, if the difference between the first ratio in the first region A1 and the first ratio in the sixth region A6 is 25% or less, the variation in lithium ion conductivity and electronic conductivity in the positive electrode active material layer 24 will be reduced, and the rate characteristics will be further improved.

[0069] The above describes the embodiments of the present invention in detail with reference to the drawings. However, each configuration and combination thereof in each embodiment is merely an example, and addition, omission, substitution, and other modifications of the configuration are possible without departing from the spirit of the present invention.

[0070] For example, although an example has been described in which the first ratio in the positive electrode active material layer satisfies a predetermined condition, the first ratio in the negative electrode active material layer may also satisfy a predetermined condition. EXAMPLES

[0071] "Example 1" First, the positive electrode was prepared by applying a positive electrode slurry to one side of an aluminum foil having a thickness of 15 μm. The positive electrode slurry was prepared by mixing a positive electrode active material, a conductive additive, a binder, and a solvent.

[0072] The positive electrode active material used was NCM811 manufactured by ECOPRO. NCM811 is a nickel-cobalt-manganese compound with a nickel:cobalt:manganese ratio of 8:1:1. Carbon black (Super-P) and Ketjen black (ECP600JD) were used as the conductive additives. Polyvinylidene fluoride (PVDF) was used as the binder. The mass ratio of NCM811 (positive electrode active material), carbon black (conductive additive), Ketjen black (conductive additive), and PVDF (binder) was 96:1:1:2. The amount of positive electrode active material carried in the positive electrode active material layer after drying was 17.4 mg / cm. 2 It was decided.

[0073] Next, the positive electrode slurry was dried. The conveying speed during drying was 5.0 m / min. The coating preheating period was 104 seconds, and the temperature was raised to 90°C. Next, the coating temperature holding period was 146 seconds, and the temperature was maintained at 90°C. After that, the coating temperature increase period was 182 seconds, and the temperature was raised to 120°C. The positive electrode slurry was dried under the above conditions to produce a positive electrode.

[0074] A glow discharge spectroscopy analysis was then performed on a positive electrode prepared under the same conditions as the positive electrode. In the glow discharge spectroscopy analysis, a first ratio was calculated by dividing the proportion of the conductive assistant by the proportion of the binder. The first ratio was calculated for each thickness width of 16.7% (about 10 μm in this example) of the total thickness of the positive electrode active material layer from the surface of the positive electrode current collector, and the overall average of these was also calculated.

[0075] Next, the negative electrode was prepared. First, negative electrode slurry was applied to one side of a copper foil with a thickness of 10 μm. The negative electrode slurry was prepared by mixing a negative electrode active material, a conductive assistant, a binder, and a solvent. Silicon was used as the negative electrode active material. Carbon black (Super-P) and Ketjen Black (ECP600JD) were used as the conductive assistant. Polyvinylidene fluoride (PVDF) was used as the binder. The mass ratio of silicon (negative electrode active material), carbon black (conductive assistant), Ketjen Black (conductive assistant), and PVDF (binder) was 96:1:1:2. The amount of negative electrode active material carried in the negative electrode active material layer after drying was 1.3 mg / cm. 2 It was decided.

[0076] (Preparation of evaluation lithium-ion secondary battery, full cell) The negative and positive electrodes thus prepared were alternately stacked with 10 μm thick polypropylene separators in between, and six negative electrodes and five positive electrodes were stacked to produce a laminate. Furthermore, in the negative electrode of the laminate, a nickel negative electrode lead was attached to the protruding end of the copper foil where the negative electrode active material layer was not provided. In the positive electrode of the laminate, an aluminum positive electrode lead was attached by an ultrasonic welding machine to the protruding end of the aluminum foil where the positive electrode active material layer was not provided.

[0077] This laminate was then inserted into an exterior body of a laminate film and heat-sealed except for one peripheral location to form a closed portion. A non-aqueous electrolyte was injected into the exterior body. The non-aqueous electrolyte was a solvent of fluoroethylene carbonate (FEC) and diethyl carbonate (DEC) in a volume ratio of 1:9, to which 1.0M (mol / L) LiPF6 was added as a lithium salt. The remaining location was then heat-sealed while reducing the pressure using a vacuum sealer to produce a lithium ion secondary battery (full cell).

[0078] The rate characteristics were measured using a secondary battery charge / discharge test device. The rate characteristics were evaluated in terms of the 5C discharge capacity retention rate (%), with the voltage range being 4.2V to 3.0V, and 1C=1000mAh per full cell design capacity. The 5C discharge capacity retention rate is the ratio of the discharge capacity when CCCV charging (constant current / constant voltage charging, end current value 0.05C) at a current value of 0.2C and discharging at a current value of 0.2C to the discharge capacity when CCCV charging (constant current / constant voltage charging, end current value 0.05C) at a current value of 0.2C and discharging at a current value of 0.2C, and is expressed by the following formula (1).

[0079] (5C capacity maintenance rate (%)) = (0.2CCCV charging / 5C discharging capacity) / (0.2CCCV charging / 0.2C discharging capacity)×100 (1)

[0080] The cycle characteristics were evaluated in an environment of 45° C. using a secondary battery charge / discharge tester (manufactured by Hokuto Denko Corporation). The cycle characteristics were evaluated by repeating 200 charge / discharge cycles of constant current / constant voltage charging at 0.5 C to 4.2 V and constant current discharging at 1 C to 3.0 V. The capacity retention rate is the discharge capacity at the 200th cycle when the discharge capacity at the initial (first) cycle is taken as 100%.

[0081] "Examples 2 to 5, Comparative Examples 1 and 2" The difference from Example 1 is that the drying conditions for the positive electrode slurry were changed. The drying conditions were changed in one of the following ways: conveying speed, drying temperature, and drying time. Details of the manufacturing conditions for Examples 1 to 5 and Comparative Examples 1 and 2 are summarized in Table 1. Drying conditions 1z to 6z in Table 1 are obtained by dividing the entire distance of the drying furnace in which the coating preheating period, coating temperature holding period, and coating temperature increase period are performed into six zones (1z to 6z). The drying temperature in Table 1 is the temperature of the coating at the center of each zone.

[0082] In Examples 2 to 5 and Comparative Examples 1 and 2, the rate characteristics and the first ratio were determined in the same manner as in Example 1.

[0083] The conditions and measurement results for Examples 1 to 5 and Comparative Examples 1 and 2 are summarized in Table 1.

[0084] [Table 1] [Explanation of symbols]

[0085] 10 Separator 20 positive electrode 22 Positive electrode current collector 24 Cathode active material layer 30 negative electrode 32 Negative electrode current collector 34 Negative electrode active material layer 40 Power generating element 50 Exterior body 52 Metal foil 54 Resin layer 60, 62 terminals 100 Lithium-ion secondary batteries A1 First region A2 Second region A3 Third region A4 Fourth region A5 Fifth region A6 Sixth region

Claims

1. A battery comprising a current collector and an active material layer in contact with at least one surface of the current collector, The active material layer includes an active material, a conductive assistant, and a binder, a first ratio, which is obtained by dividing the abundance ratio of the conductive assistant, which is determined by performing glow discharge spectroscopy on the active material layer, by the abundance ratio of the binder in a first region that is within 16.7% of the total thickness of the active material layer from the surface on the current collector side in a thickness direction of the active material layer, is 94% or more of the overall average, the first ratio in a sixth region within 16.7% of the total thickness of the active material layer in a thickness direction from a surface of the active material layer opposite to the current collector is greater than the first ratio in the first region; An electrode, wherein a difference between a ratio of the first ratio in the sixth region to the overall average and a ratio of the first ratio in the first region to the overall average is greater than or equal to 20% and less than or equal to 25%.

2. The electrode of claim 1 , wherein the first ratio in the first region is less than or equal to 130% of the overall average.

3. 3. The electrode according to claim 1, wherein the atomic ratio of carbon to fluorine in the binder is 0.5 or more and 2.1 or less.

4. A lithium ion secondary battery comprising the electrode according to any one of claims 1 to 3.

5. The method includes a conditioning step and an actual drying step, The conditioning step includes: a first step of drying a coating film containing an active material, a conductive assistant, and a binder, which is applied onto a current collector, under a plurality of conditions in which at least one of a conveying speed, a drying temperature, and a drying time is changed; a second step of analyzing each of the active material layers obtained by drying the coating film in the first step, and determining a first condition in which a first ratio, obtained by dividing the abundance ratio of the conductive assistant, obtained by performing glow discharge spectroscopy on the active material layer in a first region within 16.7% of the total thickness of the active material layer in a thickness direction from the surface of the current collector of the active material layer, by the abundance ratio of the binder, is 94% or more of an overall average, The method for producing an electrode, wherein the actual drying step is performed under the first condition.

Citation Information

Patent Citations

  • Lithium ion battery aqueous anode slurry and preparation method thereof

    CN103579579A

  • Electrode for battery

    JP2009004181A

  • Method for manufacturing nonaqueous electrolytic secondary battery, and nonaqueous electrolytic secondary battery manufactured by the method

    JP2014007037A

  • Power storage element

    JP2018174096A

  • Positive electrode active material for lithium ion secondary battery, and lithium ion secondary battery

    JP2019169286A